Ophthalmology: a dwindling specialty in Pakistan - Tariq, Moeez; Maanak Asif; Ghazala Masood Farrukh (Journal of the Pakistan Medical Association, 2023)
Madam Editor, Ophthalmology is a branch of medical science that deals with diagnosing and treating eye disorders. It comprises both the medicinal and surgical aspects of eye care. Medical students choose a specific field of their interest as their future speciality. It is the dream of every medical student to go far in his or her field of study and to make good progress. Some students choose Medicine while others opt Surgery. Even in surgery, some students choose General surgery, while others choose other surgical interests, such as Cardiac surgery, Gynaecology, Neurosurgery, etc. The same thing happens in the field of medicine i.e., they want to become Internists, Pediatricians, Dermatologists, Neurologists and Cardiologists. But the tendency of students to opt Ophthalmology is observed to be less in Pakistan (1). According to Aslam M, et al. (2011), only 1.7% of medical students in the .public sector and 3.3% of medical students in private sector medical colleges preferred Ophthalmology.(2). Another study by Hamid S et al., in 2019 conducted on the fourth and final year medical students, and house officers showed that only 3.8% of the participants were interested in Ophthalmology as a future subject of speciality, with a male to female ratio being 1:3 ,which is alarming as well (3). The main factors influencing medical students not to choose Ophthalmology include, fewer chances of residency, prolonged duration of residency, and limited opportunities in the private sector (4). Besides this, students often perceived Ophthalmology as a ‘dry subject’ by students. The basics of the eye i.e., anatomy, histology, embryology, and physiology are also extensive and difficult to be retained for a prolonged period. Poor retention of concepts can also affect the specialty preference concerning Ophthalmology among medical students. Though there are many benefits of choosing the field as a speciality, some being high income, less working hours and no duties in the night (4). Almost all cases in Ophthalmology are treated in daycare settings and the surgeries are also mainly elective procedures as there are fewer emergency calls. Moreover, sub-specialties are offered including Paediatric Ophthalmology, Orbit and Oculoplastics, and Vitreoretinal Ophthalmology (5). According to the International Council of Ophthalmology, there are 1860 ophthalmologists in Pakistan with 11 ophthalmologists per million of the population (1). There is a dire need for ophthalmologists in the country. —Continue